Ecotourism in Indonesia: Local Community Involvement and The Affecting Factors - Kia, Zakia (Universitas Muhammadiyah Yogyakarta, 2021)
Travel and tourism have become a fast-growing industry and a major source of income for many developing countries (Wood, 2002), including Indonesia. Approximately 35% of major nature tourism product portfolio is ecotourism (Kementerian Pariwisata dan Ekonomi Kreatif, 2019). Ecotourism development is based on the awareness of understanding in every environment condition which oriented in conservation and concern of the local culture as well as local civilization. Hence, the existence of community interaction is a guarantee to the sustainability of ecotourism development (Damanik, 2013; Wood, 2002). Many benefits offered by the concept of ecotourism, does not keep this concept away from several critics, related to the low of local community involvement in ecotourism management. This study aims to analyze the local community involvement as well as the affecting factors in managing the ecotourism in Indonesia by systematically reviewing 29 articles published in Sinta Ristekdiktiâ€™s accredited journals with the qualifications of Sinta 1 and Sinta 2. The discussion about local community involvement will be reviewed from the ecotourism planning level, participation in ecotourism development implementation and participation in its use (Lukman, 2017). Meanwhile, the affecting factors will be analyzed from the operational, structural and cultural perspective.Â Â The results show that the involvement of local communities in ecotourism management in Indonesia is still limited to the level of utilization. From the operational perspective, limits to local community involvement are come from limited information availability about ecotourism to local communities, centralized tourism management and the lack of coordination among stakeholders. Limited number of trained human resources, legal system that does not support the participatory practices, the uncooperative attitude of professionals and the dominance of local elite are still become the limitations to local community involvement from a structural perspective. Meanwhile, cultural barriers include apathy and a low level of public awareness of the potential benefit of ecotourism in their area. We can conclude that the empowerment efforts to local community in ecotourism destinations must be further improved. Educating the local community to understand their rights, informing them about the ecotourism management in their area would be the right first step to execute, because due to the lack of knowledge and information they have, frequently triggers disturbances from the local community which actually will thwart the ecotourism purposes.